2006
DOI: 10.1063/1.2337997
|View full text |Cite
|
Sign up to set email alerts
|

Thermal radiation and thickness fluctuations in freely suspended liquid films

Abstract: Thermal convection in a vertically suspended soap film subjected to a vertical temperature gradient is marked by intense density fluctuations ␦ 2 , uncommon to laboratory Rayleigh-Bénard convection ͑RBC͒. Such large fluctuations result from stratification in the film under the influence of gravity. Herein we present the first direct measurement of two-dimensional density fluctuations in a free-standing soap film using a single-point infrared detector. The radiation densitometer is nonintrusive and responds ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 51 publications
2
18
0
Order By: Relevance
“…To further check these results we have carried out additional experiments to measure the velocity structure functions. These results show that the velocity structure functions display Bolgiano Obukhov scaling consistent with an exponent of 3n/5 as expected and observed experimentally before 12 , 13 , 16 . Under rotation, the scaling range diminishes and the structure function exponents become smaller, contrary to 3D experiments where the exponent increases.…”
Section: Discussionsupporting
confidence: 89%
“…To further check these results we have carried out additional experiments to measure the velocity structure functions. These results show that the velocity structure functions display Bolgiano Obukhov scaling consistent with an exponent of 3n/5 as expected and observed experimentally before 12 , 13 , 16 . Under rotation, the scaling range diminishes and the structure function exponents become smaller, contrary to 3D experiments where the exponent increases.…”
Section: Discussionsupporting
confidence: 89%
“…This fact attests to both the existence of a nonuniform thickness profile in the soap film and also to the evolution of that profile with time. From a mechanical point of view, this thickness profile implies that (i) as proposed by Gibbs in 1878 [3], for any value H of the height above the bottom edge of the frame, the weight of the part of the film which lies beneath H must be counterbalanced by the local surface tension forces and (ii) since the fringe pattern in the film stretches from bottom to top, implying that the thickness gradient in the film gets smaller as H increases, the sustaining surface tension profile must both increase and saturate with H. Due to their highly interfacial nature, soap films have been in the center of numerous studies during the past few decades [1,[4][5][6][7][8][9][10][11][12][13], Early works by Mysels and co-workers [1,13,14] showed that their behaviors strongly depend on parameters such as viscosity [13] but also on the chemicals used to produce them. Specific surfactant-linked phenomena such as marginal regeneration [1,7] have also been noticed to account in phenomena such as drainage, leading to unexpected film lifetimes [1], Those studies of isolated soap films have been widely used to model global behaviors of more complex systems such as foams [15].…”
Section: Introductionmentioning
confidence: 99%
“…However only the component normal to the thickness gradient is available. An alternative is to use tracers [18,19], but they slightly deform the film which, in a vertical film, leads to artefactual gravity induced motion. Here, we propose a novel technique, based on fluorescent labeling of the flow, which overcomes these drawbacks.…”
mentioning
confidence: 99%